Visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink and preparation method thereof

By introducing visible afterglow-near-infrared dual-pass fluorescence characteristics into fluorescent anti-counterfeiting inks, the synthesis technology of carboxymidazoles and nanopolymers of olefin end groups is solved, and the problem of inks being disturbed by background under ultraviolet excitation is achieved, achieving more efficient Anti-counterfeiting performance and functionality.

CN119019889BActive Publication Date: 2025-02-14DONNELLY (CHENGDU) PRINTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411516078.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing fluorescent anti-counterfeiting inks are susceptible to paper background fluorescence and intrinsic color under ultraviolet excitation, limiting its anti-counterfeiting performance and functionality.

Method used

Using the preparation method of visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink, the synthesis of carboxymidazole, Zn-nanopolymer and Yb-nanopolymer of olefin end groups was prepared to emit near-infrared light under ultraviolet irradiation and Ink that displays visible light and long afterglow.

Benefits of technology

It effectively avoids the interference of the background fluorescence of ink and paper and the inherent color on the anti-counterfeiting performance, improves the anti-counterfeiting recognition ability of ink, and breaks the limitation that no other luminescent components cannot be added to the ink, and enhances its functionality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019889B_ABST
    Figure CN119019889B_ABST
Patent Text Reader

Abstract

The present invention discloses a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink and a preparation method thereof. The preparation method specifically comprises the following steps: step 1, preparing a carboxyimidazole with an olefin end group; step 2, synthesizing a Zn-nanopolymer according to the product obtained in step 1; step 3, preparing a Yb-nanopolymer according to the product obtained in step 1; step 4, preparing an anti-counterfeiting ink according to the products obtained in steps 2 and 3; the present invention also discloses a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink, and the near-infrared luminescence and visible light long afterglow of the ink prepared by the present invention under ultraviolet irradiation can well avoid the interference of the background fluorescence of the ink and paper and the intrinsic color of the ink and paper on the anti-counterfeiting performance of the ink.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer preparation, and relates to a visible long afterglow-near infrared double-pass fluorescent anti-counterfeiting ink and a preparation method thereof. Background Art

[0002] With the rapid development of the economy, there are more and more counterfeit and shoddy products, and people have higher and higher requirements for anti-counterfeiting. From the perspective of anti-counterfeiting mechanism, the commonly used anti-counterfeiting methods include fluorescent anti-counterfeiting, magnetic anti-counterfeiting, laser holographic image anti-counterfeiting and digital anti-counterfeiting. Fluorescent anti-counterfeiting is very suitable for high-level anti-counterfeiting because of its advantages such as fast response, permanent reversibility, and adjustable optical wavelength. However, when ink is used in the field of anti-counterfeiting, in order to avoid the color and luminescence of the ink itself not affecting the luminescence of the anti-counterfeiting ink, the color of the ink itself must be light and without interference from other luminescent colors. This will make the components that can be added to the ink very limited, thereby limiting the other functions of the ink (such as color change, sensing); in addition, fluorescent anti-counterfeiting inks are usually printed on paper, but in the papermaking industry, in order to improve the whiteness of the product, it is very common to add fluorescent brighteners, but fluorescent brighteners will also emit strong fluorescence under ultraviolet excitation, which will interfere with the anti-counterfeiting identification of the ink. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink. The ink prepared by the method has near-infrared luminescence and visible light long afterglow under ultraviolet irradiation, which can effectively avoid the interference of the background fluorescence of the ink and paper and the intrinsic color of the ink and paper on the anti-counterfeiting performance of the ink.

[0004] Another object of the present invention is to provide a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink.

[0005] The first technical solution adopted by the present invention is a method for preparing a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink, which specifically comprises the following steps:

[0006] Step 1, preparing olefin-terminated carboxyimidazole;

[0007] Step 2, synthesizing Zn-nanopolymer according to the product obtained in step 1;

[0008] Step 3, preparing Yb-nanopolymer according to the product obtained in step 1;

[0009] Step 4, preparing anti-counterfeiting ink according to the products obtained in steps 2 and 3.

[0010] The first technical solution of the present invention is also characterized in that:

[0011] The specific process of step 1 is:

[0012] Step 1.1, dissolving 10-30 g of dicarboxy imidazole in 20-60 mL of tetrahydrofuran solution, then adding 0.2-0.6 g of catalyst and 0.2-0.6 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0013] Step 1.2, dissolving 5-15 g of 4-vinylaniline in 20-60 mL of tetrahydrofuran solution to obtain a 4-vinylaniline solution;

[0014] Step 1.3, add the 4-vinylaniline solution obtained in step 1.2 dropwise to the dicarboxyimidazole solution obtained in step 1.1, the addition time is 15-30 min, react at 60-120°C for 12-18h, use ethyl acetate / n-hexane as the mobile phase, and separate by column to obtain white olefin-terminated carboxyimidazole.

[0015] In step 1.1, the catalyst is 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide.

[0016] The specific process of step 2 is:

[0017] Step 2.1, 10-30 g of olefin-terminated carboxyimidazole and 50-150 g of glycidyl acrylate are dissolved in 50-100 mL of DMF solvent; then 0.03-0.09 g of azobisisobutyronitrile is added, and the temperature is raised to 65-90° C. under nitrogen conditions for reaction for 12-18 hours. After the reaction is completed, the temperature is lowered to room temperature, 20-60 mL of HCl aqueous solution with a pH of 5-6 is added to the reaction solution, and the reaction solution is directly poured into 500-1000 mL of industrial alcohol to precipitate the product to obtain a polymer precursor;

[0018] Step 2.2, take 5-15g of polymer precursor and dissolve it in 5-10L of deionized water, let it stand for 12-18h,

[0019] A low-concentration polymer solution is obtained;

[0020] Step 2.3, weigh 0.4-1.2 g of zinc chloride and dissolve it in 0.5-1.5 L of deionized water to obtain a zinc chloride solution;

[0021] Step 2.4, adding the zinc chloride solution obtained in step 2.3 dropwise to the low-concentration polymer solution prepared in step 2.2 for reaction for 2 to 4 hours, stirring at a speed of 900-1200 r / min during the reaction, and dialyzing the reaction solution with a 7000-10000Da dialysis bag after the reaction to remove unreacted substances;

[0022] Step 2.5, freeze-drying the product obtained in step 2.4 at -70°C to obtain white Zn-nanopolymer.

[0023] The specific process of step 3 is:

[0024] Step 3.1, add 10-30 g of olefin-terminated carboxyimidazole and 50-150 mL of styrene to 50-100 mL of DMF solvent, then add 0.03-0.09 g of azobisisobutyronitrile, raise the temperature to 65-90° C. under nitrogen conditions, react for 12-18 hours, and after the reaction is completed, lower the temperature to room temperature, and directly pour the reaction solution into 500-1000 mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer;

[0025] Step 3.2, dissolving 5-15 g of an oil-soluble polymer in 5-10 L of DMF and standing for 12-18 h to obtain a low-concentration polymer solution;

[0026] Step 3.3, weigh 0.4-1.2 g of ytterbium chloride and dissolve it in 0.5-1.5 L of DMF to obtain an ytterbium chloride solution;

[0027] Step 3.4, adding the ytterbium chloride solution obtained in step 3.3 dropwise to the low-concentration polymer solution prepared in step 3.2 for reaction for 2 to 4 hours; stirring at a speed of 900-1200 r / min during the reaction, and dialyzing the reaction solution with a 7000-10000Da dialysis bag after the reaction is completed to remove unreacted substances;

[0028] Step 3.5, freeze-drying the product obtained in step 3.4 at -70°C to obtain white Yb-nanopolymer.

[0029] The specific process of step 4 is:

[0030] Take 1-2g of Zn-nanopolymer, 2-4g of Yb-nanopolymer, 0.3-0.6g of boric acid, 1-2mL of toluene, 1-2mL of ethyl acetate and 5-10mL of PU tactile matt oil, mix and stir for 10-20min to obtain anti-counterfeiting ink.

[0031] The second technical solution adopted by the present invention is that the visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink is prepared by the preparation method of the visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink.

[0032] The beneficial effects of the present invention are as follows:

[0033] (1) The present invention has developed a visible long afterglow-near infrared dual-channel anti-counterfeiting ink with excellent rheological properties. The near-infrared luminescence and visible long afterglow under ultraviolet irradiation can effectively avoid the interference of background fluorescence and intrinsic color of ink and paper.

[0034] (2) The present invention constructs a coordinating polymer material, which is used to bind Zn 2+ and Yb 3+ The nano-polymer material is obtained by ion coordination, and visible long afterglow luminescence and near-infrared luminescence are constructed, which can effectively avoid the influence of background light or fluorescent brightener on the optical anti-counterfeiting performance of the material under ultraviolet light irradiation.

[0035] (3) The present invention uses polymers to prepare anti-counterfeiting materials, avoiding the large particle size and rheological problems of inorganic anti-counterfeiting materials; near-infrared luminescence under ultraviolet excitation and long afterglow of visible light are used to achieve dual-channel anti-counterfeiting, greatly improving the anti-counterfeiting performance; the anti-counterfeiting luminescence of fluorescent anti-counterfeiting ink is not affected by the background fluorescence of paper. This breaks the restriction that other components containing ultraviolet absorption or fluorescence emission cannot be added to anti-counterfeiting inks, so that the ink can have other functions (such as color change, sensing) by adding a variety of additives while having anti-counterfeiting functions. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a near-infrared emission spectrum diagram of Example 1 of the preparation method of the visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink of the present invention and Comparative Examples 1 and 4. DETAILED DESCRIPTION

[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0038] The preparation method of the visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink of the present invention specifically comprises the following steps:

[0039] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0040] Step 1.1, dissolving 10-30 g of dicarboxy imidazole in 20-60 mL of tetrahydrofuran solution, then adding 0.2-0.6 g of a catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.2-0.6 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0041] Step 1.2, dissolving 5-15 g of 4-vinylaniline in 20-60 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0042] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 15-30 min, heat to 60-120°C and react for 12-18 h. Use ethyl acetate / n-hexane (volume ratio 1:1) as mobile phase, and separate by column to obtain white olefin-terminated carboxyimidazole.

[0043] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0044] Step 2.1, take 10-30g of olefin-terminated carboxyimidazole and 50-150g of glycidyl acrylate and dissolve them in 50-100mL of DMF solvent. Then add 0.03-0.09g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65-90°C and react for 12-18h. After the reaction is completed, the temperature is lowered to room temperature. 20-60mL of HCl aqueous solution with a pH of 5-6 is added to the reaction solution. The reaction solution is directly poured into 500-1000mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0045] Step 2.2, dissolve 5-15 g of polymer precursor in 5-10 L of deionized water and let stand for 12-18 hours to obtain a low-concentration polymer solution;

[0046] Step 2.3, weigh 0.4-1.2 g of zinc chloride and dissolve it in 0.5-1.5 L of deionized water to obtain a zinc chloride solution;

[0047] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (900-1200 r / min) at room temperature (addition time 30-60 min), and the reaction is continued for 2-4 hours after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000-10000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze drying to obtain white Zn-nanopolymer.

[0048] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0049] Step 3.1, add 10-30g of olefin-terminated carboxyimidazole and 50-150mL of styrene to 50-100mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03-0.09g of azobisisobutyronitrile. Under nitrogen conditions, increase the temperature to 65-90°C and react for 12-18h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500-1000mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0050] Step 3.2, dissolve 5-15 g of the oil-soluble polymer in 5-10 L of DMF and let stand for 12-18 hours to obtain a low-concentration polymer solution;

[0051] Step 3.3, weigh 0.4-1.2 g of ytterbium chloride and dissolve it in 0.5-1.5 L of DMF to obtain an ytterbium chloride solution;

[0052] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (900-1200 r / min) at room temperature (addition time 30-60 min), and the reaction is continued for 2-4 hours after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000-10000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze drying to obtain white Yb-nanopolymer.

[0053] Step 4, preparing anti-counterfeiting ink, specifically:

[0054] Take 1-2g of Zn-nanopolymer, 2-4g of Yb-nanopolymer, 0.3-0.6g of boric acid, 1-2mL of toluene, 1-2mL of ethyl acetate and 5-10mL of PU touch matt oil (polyurethane matt oil), stir well for 10-20min to obtain anti-counterfeiting ink.

[0055] The ink is printed on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of the fluorescent brightener KB.

[0056] Example 1

[0057] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0058] Step 1.1, dissolving 10 g of dicarboxy imidazole in 20 mL of tetrahydrofuran solution, then adding 0.2 g of catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.2 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0059] Step 1.2, dissolving 5 g of 4-vinylaniline in 20 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0060] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 15 min, heat to 60°C and react for 12 h. Use ethyl acetate / n-hexane (volume ratio 1:1) as mobile phase, column separation to obtain white olefin-terminated carboxyimidazole.

[0061] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0062] Step 2.1, take 10g of olefin-terminated carboxyimidazole and 50g of glycidyl acrylate and dissolve them in 50mL of DMF solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C and react for 12h. After the reaction is completed, the temperature is lowered to room temperature. Add 20mL of HCl aqueous solution with a pH of 5 to the reaction solution, and directly pour 500mL of industrial alcohol into the reaction solution to precipitate the product to obtain a polymer precursor.

[0063] Step 2.2, dissolving 5 g of polymer precursor in 5 L of deionized water and letting it stand for 12 h to obtain a low-concentration polymer solution;

[0064] Step 2.3, weigh 0.4 g of zinc chloride and dissolve it in 0.5 L of deionized water to obtain a zinc chloride solution;

[0065] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (900 r / min) at room temperature (addition time 30 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Zn-nanopolymer.

[0066] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0067] Step 3.1, add 10g of olefin-terminated carboxyimidazole and 50mL of styrene to 50mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C for 12h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0068] Step 3.2, dissolve 5 g of the oil-soluble polymer in 5 L of DMF and let stand for 12 h to obtain a low-concentration polymer solution;

[0069] Step 3.3, weigh 0.4 g of ytterbium chloride and dissolve it in 0.5 L of DMF to obtain an ytterbium chloride solution;

[0070] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (900 r / min) at room temperature (addition time: 30 min). After the addition is completed, the reaction is continued for 2 h. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then freeze-dried at -70°C to obtain white Yb-nanopolymer.

[0071] Step 4, preparing anti-counterfeiting ink, specifically:

[0072] Take 1g of Zn-nanopolymer, 2g of Yb-nanopolymer, 0.3g of boric acid, 1mL of toluene, 1mL of ethyl acetate and 5mL of PU matte oil (polyurethane matte oil), stir them thoroughly for 10min to obtain anti-counterfeiting ink. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

[0073] Comparative Example 1 (Zn-nanopolymer preparation process is prepared according to the process of Yb-nanomaterial, and the visible light afterglow becomes shorter)

[0074] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0075] Step 1.1, dissolving 10 g of dicarboxy imidazole in 20 mL of tetrahydrofuran solution, then adding 0.2 g of catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.2 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0076] Step 1.2, dissolving 5 g of 4-vinylaniline in 20 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0077] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 15 min, heat to 60°C and react for 12 h. Use ethyl acetate / n-hexane (volume ratio 1:1) as mobile phase, column separation to obtain white olefin-terminated carboxyimidazole.

[0078] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0079] Step 2.1, take 10g of olefin-terminated carboxyimidazole and 50mL of styrene and add them to 50mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C and react for 12h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer;

[0080] Step 2.2, dissolve 5 g of oil-soluble polymer in 5 L of DMF and let stand for 12 h to obtain a low-concentration polymer solution;

[0081] Step 2.3, weigh 0.4 g of zinc chloride and dissolve it in 0.5 L of DMF to obtain a zinc chloride solution;

[0082] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (900 r / min) at room temperature (addition time 30 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Zn-nanopolymer.

[0083] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0084] Step 3.1, add 10g of olefin-terminated carboxyimidazole and 50mL of styrene to 50mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, increase the temperature to 65 and react for 12h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0085] Step 3.2, dissolve 5 g of the oil-soluble polymer in 5 L of DMF and let stand for 12 h to obtain a low-concentration polymer solution;

[0086] Step 3.3, weigh 0.4 g of ytterbium chloride and dissolve it in 0.5 L of DMF to obtain an ytterbium chloride solution;

[0087] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (900 r / min) at room temperature (addition time: 30 min). After the addition is completed, the reaction is continued for 2 h. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then freeze-dried at -70°C to obtain white Yb-nanopolymer.

[0088] Step 4, preparing anti-counterfeiting ink, specifically:

[0089] Take 1g of Zn-nanopolymer, 2g of Yb-nanopolymer, 0.3g of boric acid, 1mL of toluene, 1mL of ethyl acetate and 5mL of PU matte oil (polyurethane matte oil), stir them thoroughly for 10min to obtain anti-counterfeiting ink. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

[0090] Comparative Example 2 (Yb-nanopolymer preparation process replaced by Zn-nanomaterial process, no near-infrared luminescence)

[0091] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0092] Step 1.1, dissolving 10 g of dicarboxy imidazole in 20 mL of tetrahydrofuran solution, then adding 0.2 g of catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.2 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0093] Step 1.2, dissolving 5 g of 4-vinylaniline in 20 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0094] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 15 min, heat to 60°C and react for 12 h. Use ethyl acetate / n-hexane (volume ratio 1:1) as mobile phase, column separation to obtain white olefin-terminated carboxyimidazole.

[0095] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0096] Step 2.1, take 10g of olefin-terminated carboxyimidazole and 50g of glycidyl acrylate and dissolve them in 50mL of DMF solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C and react for 12h. After the reaction is completed, the temperature is lowered to room temperature. Add 20mL of HCl aqueous solution with a pH of 5 to the reaction solution, and directly pour the reaction solution into 500mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0097] Step 2.2, dissolving 5 g of polymer precursor in 5 L of deionized water and letting it stand for 12 h to obtain a low-concentration polymer solution;

[0098] Step 2.3, weigh 0.4 g of zinc chloride and dissolve it in 0.5 L of deionized water to obtain a zinc chloride solution;

[0099] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (900 r / min) at room temperature (addition time 30 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Zn-nanopolymer.

[0100] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0101] Step 3.1, take 10g of olefin-terminated carboxyimidazole and 50mL of glycidyl acrylate and add them to 50mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C for 12h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0102] Step 3.2, dissolve 5 g of polymer precursor in 5 L of deionized water and let stand for 12 h to obtain a low-concentration polymer solution;

[0103] Step 3.3, weigh 0.4 g of ytterbium chloride and dissolve it in 0.5 L of deionized water to obtain an ytterbium chloride solution;

[0104] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (900 r / min) at room temperature (addition time: 30 min). After the addition is completed, the reaction is continued for 2 h. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then freeze-dried at -70°C to obtain white Yb-nanopolymer.

[0105] Step 4, preparing anti-counterfeiting ink, specifically:

[0106] Take 1g of Zn-nanopolymer, 2g of Yb-nanopolymer, 0.3g of boric acid, 1mL of toluene, 1mL of ethyl acetate and 5mL of PU matte oil (polyurethane matte oil), stir them thoroughly for 10min to obtain anti-counterfeiting ink. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

[0107] Comparative Example 3 (The preparation processes of Zn-nanopolymer and Yb-nanopolymer are exchanged, and the long afterglow becomes shorter and there is no near-infrared light)

[0108] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0109] Step 1.1, dissolving 10 g of dicarboxy imidazole in 20 mL of tetrahydrofuran solution, then adding 0.2 g of catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.2 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0110] Step 1.2, dissolving 5 g of 4-vinylaniline in 20 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0111] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 15 min, heat to 60°C and react for 12 h. Use ethyl acetate / n-hexane (volume ratio 1:1) as mobile phase, column separation to obtain white olefin-terminated carboxyimidazole.

[0112] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0113] Step 2.1, add 10g of olefin-terminated carboxyimidazole and 50mL of styrene to 50mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C for 12h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0114] Step 2.2, dissolve 5 g of oil-soluble polymer in 5 L of DMF and let stand for 12 h to obtain a low-concentration polymer solution;

[0115] Step 2.3, weigh 0.4 g of zinc chloride and dissolve it in 0.5 L of DMF to obtain a zinc chloride solution;

[0116] Step 2.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (900 r / min) at room temperature (addition time: 30 min). After the addition is completed, the reaction is continued for 2 h. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then freeze-dried at -70°C to obtain white Zn-nanopolymer.

[0117] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0118] Step 3.1, take 10g of olefin-terminated carboxyimidazole and 50g of glycidyl acrylate and dissolve them in 50mL of DMF solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C and react for 12h. After the reaction is completed, the temperature is lowered to room temperature. 20mL of HCl aqueous solution with a pH of 5 is added to the reaction solution. The reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0119] Step 3.2, dissolve 5 g of polymer precursor in 5 L of deionized water and let stand for 12 h to obtain a low-concentration polymer solution;

[0120] Step 3.3, weigh 0.4 g of ytterbium chloride and dissolve it in 0.5 L of deionized water to obtain an ytterbium chloride solution;

[0121] Step 3.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (900 r / min) at room temperature (addition time 30 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Yb-nanopolymer.

[0122] Step 4, preparing anti-counterfeiting ink, specifically:

[0123] Take 1g of Zn-nanopolymer, 2g of Yb-nanopolymer, 0.3g of boric acid, 1mL of toluene, 1mL of ethyl acetate and 5mL of PU matte oil (polyurethane matte oil), stir them thoroughly for 10min to obtain anti-counterfeiting ink. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

[0124] Comparative Example 4 (boric acid was not added to the ink, and the long afterglow became shorter)

[0125] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0126] Step 1.1, dissolving 10 g of dicarboxy imidazole in 20 mL of tetrahydrofuran solution, then adding 0.2 g of catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.2 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0127] Step 1.2, dissolving 5 g of 4-vinylaniline in 20 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0128] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 15 min, heat to 60°C and react for 12 h. Use ethyl acetate / n-hexane (volume ratio 1:1) as mobile phase, column separation to obtain white olefin-terminated carboxyimidazole.

[0129] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0130] Step 2.1, take 10g of olefin-terminated carboxyimidazole and 50g of glycidyl acrylate and dissolve them in 50mL of DMF solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C and react for 12h. After the reaction is completed, the temperature is lowered to room temperature. Add 20mL of HCl aqueous solution with a pH of 5 to the reaction solution, and directly pour the reaction solution into 500mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0131] Step 2.2, dissolving 5 g of polymer precursor in 5 L of deionized water and letting it stand for 12 h to obtain a low-concentration polymer solution;

[0132] Step 2.3, weigh 0.4 g of zinc chloride and dissolve it in 0.5 L of deionized water to obtain a zinc chloride solution;

[0133] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (900 r / min) at room temperature (addition time 30 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Zn-nanopolymer.

[0134] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0135] Step 3.1, add 10g of olefin-terminated carboxyimidazole and 50mL of styrene to 50mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, increase the temperature to 65 and react for 12h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0136] Step 3.2, dissolve 5 g of the oil-soluble polymer in 5 L of DMF and let stand for 12 h to obtain a low-concentration polymer solution;

[0137] Step 3.3, weigh 0.4 g of ytterbium chloride and dissolve it in 0.5 L of DMF to obtain an ytterbium chloride solution;

[0138] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (900 r / min) at room temperature (addition time: 30 min). After the addition is completed, the reaction is continued for 2 h. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then freeze-dried at -70°C to obtain white Yb-nanopolymer.

[0139] Step 4, preparing anti-counterfeiting ink, specifically:

[0140] Take 1g of Zn-nanopolymer, 2g of Yb-nanopolymer, 1mL of toluene, 1mL of ethyl acetate and 5mL of PU touch matt oil, stir them thoroughly for 10min. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

[0141] Comparative Example 5 (When dicarboxy imidazole is replaced with 4-imidazolecarboxylic acid, Zn-nanopolymer and Yb-nanopolymer cannot be constructed, and there is no visible long afterglow and near-infrared luminescence)

[0142] Step 1, preparation of olefin-terminated imidazole, specifically:

[0143] Step 1.1, dissolving 10 g of 4-imidazolecarboxylic acid in 20 mL of tetrahydrofuran solution, and then adding 0.2 g of 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC) as a catalyst and 0.2 g of N-hydroxysuccinimide to obtain a mixed solution containing 4-imidazolecarboxylic acid;

[0144] Step 1.2, dissolving 5 g of 4-vinylaniline in 20 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0145] Step 1.3, slowly add the 4-vinylaniline solution to the mixed solution containing 4-imidazolecarboxylic acid, the addition time is 15 min, the temperature is heated to 60°C and the reaction is carried out for 12 h. Ethyl acetate / n-hexane (volume ratio is 1:1) is used as the mobile phase, and the white olefin-terminated imidazole is separated by column separation.

[0146] Step 2, synthesis of Zn-polymer, the specific process is:

[0147] Step 2.1, take 10g of olefin-terminated imidazole and 50g of glycidyl acrylate and dissolve them in 50mL of DMF solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65°C and react for 12h. After the reaction is completed, the temperature is lowered to room temperature. Add 20mL of HCl aqueous solution with a pH of 5 to the reaction solution, and directly pour the reaction solution into 500mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0148] Step 2.2, dissolving 5 g of polymer precursor in 5 L of deionized water and letting it stand for 12 h to obtain a low-concentration polymer solution;

[0149] Step 2.3, weigh 0.4 g of zinc chloride and dissolve it in 0.5 L of deionized water to obtain a zinc chloride solution;

[0150] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (900 r / min) at room temperature (addition time 30 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain a white Zn-polymer.

[0151] Step 3, synthesis of Yb-polymer, the specific process is:

[0152] Step 3.1, add 10g of olefin-terminated imidazole and 50mL of styrene to 50mL of DMF (N,N-dimethylformamide) solvent. Then add 0.03g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 65 and react for 12h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 500mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0153] Step 3.2, dissolve 5 g of the oil-soluble polymer in 5 L of DMF and let stand for 12 h to obtain a low-concentration polymer solution;

[0154] Step 3.3, weigh 0.4 g of ytterbium chloride and dissolve it in 0.5 L of DMF to obtain an ytterbium chloride solution;

[0155] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (900 r / min) at room temperature (addition time: 30 min). After the addition is completed, the reaction is continued for 2 h. After the reaction is completed, the reaction solution is dialyzed using a 7000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then freeze-dried at -70°C to obtain a white Yb-polymer.

[0156] Step 4, preparation of ink, specifically:

[0157] Take 1g of Zn-polymer, 2g of Yb-polymer, 0.3g of boric acid, 1mL of toluene, 1mL of ethyl acetate and 5mL of PU touch matt oil, stir them thoroughly for 10min. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

[0158] Results and Discussion

[0159] Table 1, Performance Tests of Example 1 and Comparative Examples 1-5

[0160] UV emission wavelength of paper (nm) UV ink emission wavelength (nm) Long afterglow color (turn off UV after 1min of UV irradiation) Long afterglow time (s) Near infrared wavelength (nm) Example 1 430 430 450 5 980 Comparative Example 1 430 430 450 1.5 980 Comparative Example 2 430 430 450 5 none Comparative Example 3 430 430 450 1.5 none Comparative Example 4 430 430 450 1 980 Comparative Example 5 430 - - - -

[0161] As shown in Table 1, under 365nm ultraviolet irradiation, the 430nm background fluorescence of paper can be seen in Example 1 and Comparative Examples 1-5. At the same time, the 430nm luminescence emitted by the ink can be seen in Example 1 and Comparative Examples 1-4. Due to the overlap of the background blue light of the paper and the 430nm (blue light) emitted by the ink, its anti-counterfeiting performance cannot be identified.

[0162] The long afterglow phenomenon of the ink can be seen in both Example 1 and Comparative Examples 1-4, but the difference is that the duration of the long afterglow is different. For Comparative Example 1, since the Zn-nanopolymer preparation process is replaced by the Yb-nanomaterial process, the Zn-nanopolymer lacks hydroxyl groups in the polymer skeleton and cannot effectively form a stable triplet transition. It should be noted that the UV irradiation is 430nm blue light. Since the background fluorescence in the paper has no long afterglow effect, after turning off the UV lamp, there is no background fluorescence, only the long afterglow of the ink, which can be identified by the naked eye, which is conducive to its application in anti-counterfeiting.

[0163] For comparative example 3, the preparation processes of Zn-nanopolymer and Yb-nanopolymer were exchanged. After the exchange, the prepared Zn-nanopolymer lacked hydroxyl groups in the polymer skeleton, and could not effectively form stable triplet transition luminescence, and the long afterglow time became shorter.

[0164] Compared with comparative example 4, boric acid can form a stable ester bond with the glycidyl ester functional group in the polymer skeleton, which can strengthen the triplet transition luminescence and increase the afterglow time.

[0165] like Figure 1As shown, in Example 1 and Comparative Examples 1 and 4, the characteristic near-infrared luminescence (em = 980 nm) of rare earth ions can be seen. On the contrary, in Comparative Example 2, the Yb-nanopolymer preparation process is replaced by the Zn-nanomaterial process. The Yb polymer skeleton contains a large number of hydroxyls, and the near-infrared luminescence is very sensitive to the hydroxyl oscillation group, resulting in near-infrared luminescence quenching. Similarly, the Yb polymer skeleton in Comparative Example 3 also contains a large number of hydroxyls to quench the near-infrared luminescence. It should be pointed out that the near-infrared is invisible to the naked eye and requires instrument detection, which improves the anti-counterfeiting performance.

[0166] In Comparative Example 5, when dicarboxy imidazole is replaced by 4-imidazole carboxylic acid, the prepared polymer precursor lacks carboxyl groups, and Zn and Yb cannot be coordinated and chelated. Therefore, Zn-nanopolymer and Yb-nanopolymer cannot be constructed. Therefore, the prepared ink has no 430nm blue light emission, no long afterglow, and no near-infrared light emission is detected when irradiated with ultraviolet light.

[0167] Table 2. Nanoparticle radius in Example 1 and Comparative Example 5

[0168]

[0169] As shown in Table 2, the hydrodynamic radius of the polymer precursor is 29 nm. In Example 1 and Comparative Examples 1-4, the hydrodynamic radius of the Zn-nanopolymer and the Yb-nanopolymer is smaller than that of the polymer precursor. This is because the polymer precursor and the metal ion Zn 2+ and Yb 3+ The coordination chelation occurs, so that Example 1 has a long afterglow time and near-infrared luminescence. In a dilute solution, the polymer precursor is a straight chain. After coordination folding, the straight chain becomes curled and the hydrodynamic radius becomes smaller. It is worth noting that the hydrodynamic radius of Yb nanopolymers is smaller than that of Zn nanopolymers. This is because Yb 3+ The ion is trivalent, and can form three-fold coordination with the polymer precursor. The polymer precursor folds more times and the ball is more compact. In comparative example 5, the polymer precursor lacks carboxyl groups and cannot form nanomaterials by coordination folding. Therefore, the hydraulic radius does not change much compared with the precursor. At this time, the ink of comparative example 5 does not emit light, and there is no long afterglow phenomenon and near-infrared luminescence.

[0170] Example 2

[0171] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0172] Step 1.1, dissolving 20 g of dicarboxy imidazole in 40 mL of tetrahydrofuran solution, then adding 0.4 g of catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.4 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution;

[0173] Step 1.2, dissolving 10 g of 4-vinylaniline in 40 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0174] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 20 min, heat to 100°C and react for 16 h. Use ethyl acetate / n-hexane (volume ratio 1:1) as mobile phase, column separation to obtain white olefin-terminated carboxyimidazole.

[0175] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0176] Step 2.1, take 20g of olefin-terminated carboxyimidazole and 100g of glycidyl acrylate and dissolve them in 80mL of DMF solvent. Then add 0.06g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 80°C and react for 16h. After the reaction is completed, the temperature is lowered to room temperature. 40mL of HCl aqueous solution with a pH of 5 is added to the reaction solution. The reaction solution is directly poured into 800mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0177] Step 2.2, dissolving 10 g of polymer precursor in 8 L of deionized water and letting it stand for 16 h to obtain a low-concentration polymer solution;

[0178] Step 2.3, weigh 0.8 g of zinc chloride and dissolve it in 0.8 L of deionized water to obtain a zinc chloride solution;

[0179] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (1000 r / min) and room temperature conditions (addition time 40 min), and the reaction is continued for 3 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 9000Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Zn-nanopolymer.

[0180] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0181] Step 3.1, add 20g of olefin-terminated carboxyimidazole and 100mL of styrene to 80mL of DMF (N,N-dimethylformamide) solvent. Then add 0.06g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 85°C and react for 16h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 800mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0182] Step 3.2, dissolving 10 g of the oil-soluble polymer in 8 L of DMF and letting it stand for 16 h to obtain a low-concentration polymer solution;

[0183] Step 3.3, weigh 0.8 g of ytterbium chloride and dissolve it in 1.2 L of DMF to obtain an ytterbium chloride solution;

[0184] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (1000 r / min) at room temperature (addition time 40 min), and the reaction is continued for 3 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 9000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Yb-nanopolymer.

[0185] Step 4, preparing anti-counterfeiting ink, specifically:

[0186] Take 1.5g of Zn-nanopolymer, 3g of Yb-nanopolymer, 0.4g of boric acid, 1.5mL of toluene, 1.5mL of ethyl acetate and 8mL of PU matte oil (polyurethane matte oil), stir them thoroughly for 15min to obtain anti-counterfeiting ink. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

[0187] Example 3

[0188] Step 1, preparation of olefin-terminated carboxyimidazole, specifically:

[0189] Step 1.1, 30 g of dicarboxy imidazole was dissolved in 60 mL of tetrahydrofuran solution, and then 0.6 g of catalyst (1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC)) and 0.6 g of N-hydroxysuccinimide were added, and the mixture was mixed to obtain a dicarboxy imidazole solution;

[0190] Step 1.2, dissolving 15 g of 4-vinylaniline in 60 mL of tetrahydrofuran solution to obtain a vinylaniline solution;

[0191] Step 1.3, add 4-vinylaniline solution dropwise to dicarboxyimidazole solution for 30 minutes, heat to 120℃ and react for 18 hours. Use ethyl acetate / n-hexane (volume ratio of 1:1) as mobile phase, and separate by column to obtain white olefin-terminated carboxyimidazole.

[0192] Step 2, synthesis of Zn-nanopolymer, the specific process is:

[0193] Step 2.1, take 30g of olefin-terminated carboxyimidazole and 150g of glycidyl acrylate and dissolve them in 100mL of DMF solvent. Then add 0.09g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 90°C and react for 18h. After the reaction is completed, the temperature is lowered to room temperature. 60mL of HCl aqueous solution with a pH of 6 is added to the reaction solution. The reaction solution is directly poured into 1000mL of industrial alcohol to precipitate the product to obtain a polymer precursor.

[0194] Step 2.2, dissolving 15 g of polymer precursor in 10 L of deionized water and letting it stand for 18 h to obtain a low-concentration polymer solution;

[0195] Step 2.3, weigh 1.2 g of zinc chloride and dissolve it in 1.5 L of deionized water to obtain a zinc chloride solution;

[0196] Step 2.4, the zinc chloride solution is added dropwise to the low-concentration polymer solution obtained in step 2.2 under rapid stirring (1200 r / min) and room temperature conditions (addition time 60 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 10000 Da dialysis bag to remove unreacted zinc chloride and small-sized nanomaterials (less than 7000 Da), and then placed in -70 ° C freeze-dried to obtain white Zn-nanopolymer.

[0197] Step 3, synthesis of Yb-nanopolymer, the specific process is:

[0198] Step 3.1, add 30g of olefin-terminated carboxyimidazole and 150mL of styrene to 100mL of DMF (N,N-dimethylformamide) solvent. Then add 0.09g of azobisisobutyronitrile. Under nitrogen conditions, raise the temperature to 90°C for 18h. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is directly poured into 1000mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer.

[0199] Step 3.2, dissolve 15 g of the oil-soluble polymer in 10 L of DMF and let stand for 18 h to obtain a low-concentration polymer solution;

[0200] Step 3.3, weigh 1.2 g of ytterbium chloride and dissolve it in 1.5 L of DMF to obtain an ytterbium chloride solution;

[0201] Step 3.4, the ytterbium chloride solution is added dropwise to the low-concentration polymer solution obtained in step 3.2 under rapid stirring (1200 r / min) at room temperature (addition time 60 min), and the reaction is continued for 2 h after the addition is completed. After the reaction is completed, the reaction solution is dialyzed using a 10000Da dialysis bag to remove unreacted ytterbium chloride and small-sized nanomaterials (less than 7000Da), and then placed in -70°C for freeze-drying to obtain white Yb-nanopolymer.

[0202] Step 4, preparing anti-counterfeiting ink, specifically:

[0203] Take 2g of Zn-nanopolymer, 4g of Yb-nanopolymer, 0.6g of boric acid, 2mL of toluene, 2mL of ethyl acetate and 10mL of PU matte oil (polyurethane matte oil), stir thoroughly for 20min to obtain anti-counterfeiting ink. Then print the ink on A4 printing paper (fluorescent brightener KB) by screen printing. Background fluorescence can be observed under ultraviolet irradiation, and its luminescent color is the luminescent color of fluorescent brightener KB.

Claims

1. A method for preparing a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink, characterized in that: The specific steps include: Step 1, preparing olefin-terminated carboxyimidazole; Step 2, synthesizing Zn-nanopolymer according to the product obtained in step 1; Step 3, preparing Yb-nanopolymer according to the product obtained in step 1; Step 4, preparing anti-counterfeiting ink according to the products obtained in steps 2 and 3, The specific process of step 1 is as follows: Step 1.1, dissolving 10-30 g of dicarboxy imidazole in 20-60 mL of tetrahydrofuran solution, then adding 0.2-0.6 g of catalyst and 0.2-0.6 g of N-hydroxysuccinimide, and mixing well to obtain a dicarboxy imidazole solution; Step 1.2, dissolving 5-15 g of 4-vinylaniline in 20-60 mL of tetrahydrofuran solution to obtain a 4-vinylaniline solution; Step 1.3, add the 4-vinylaniline solution obtained in step 1.2 dropwise to the dicarboxyimidazole solution obtained in step 1.1, the addition time is 15-30 min, at 60-120 ℃ The reaction was carried out at room temperature for 12-18 hours, and ethyl acetate / n-hexane was used as the mobile phase. The white olefin-terminated carboxy imidazole was separated by column. The specific process of step 2 is: Step 2.1, 10-30 g of olefin-terminated carboxyimidazole and 50-150 g of glycidyl acrylate are dissolved in 50-100 mL of DMF solvent; then 0.03-0.09 g of azobisisobutyronitrile is added, and the temperature is raised to 65-90° C. under nitrogen conditions for reaction for 12-18 hours. After the reaction is completed, the temperature is lowered to room temperature, 20-60 mL of HCl aqueous solution with a pH of 5-6 is added to the reaction solution, and the reaction solution is directly poured into 500-1000 mL of industrial alcohol to precipitate the product to obtain a polymer precursor; Step 2.2, dissolve 5-15 g of polymer precursor in 5-10 L of deionized water and let stand for 12-18 hours to obtain a low-concentration polymer solution; Step 2.3, weigh 0.4-1.2 g of zinc chloride and dissolve it in 0.5-1.5 L of deionized water to obtain a zinc chloride solution; Step 2.4, adding the zinc chloride solution obtained in step 2.3 dropwise to the low-concentration polymer solution prepared in step 2.2 for reaction for 2 to 4 hours, stirring at a speed of 900-1200 r / min during the reaction, and dialyzing the reaction solution with a 7000-10000Da dialysis bag after the reaction to remove unreacted substances; Step 2.5, freeze-dry the product obtained in step 2.4 at -70°C to obtain white Zn-nanopolymer. The specific process of step 3 is as follows: Step 3.1, add 10-30 g of olefin-terminated carboxyimidazole and 50-150 mL of styrene to 50-100 mL of DMF solvent, then add 0.03-0.09 g of azobisisobutyronitrile, raise the temperature to 65-90° C. under nitrogen conditions, react for 12-18 hours, and after the reaction is completed, lower the temperature to room temperature, and directly pour the reaction solution into 500-1000 mL of industrial alcohol to precipitate the product to obtain an oil-soluble polymer; Step 3.2, dissolving 5-15 g of an oil-soluble polymer in 5-10 L of DMF and standing for 12-18 h to obtain a low-concentration polymer solution; Step 3.3, weigh 0.4-1.2 g of ytterbium chloride and dissolve it in 0.5-1.5 L of DMF to obtain an ytterbium chloride solution; Step 3.4, adding the ytterbium chloride solution obtained in step 3.3 dropwise to the low-concentration polymer solution prepared in step 3.2 for reaction for 2 to 4 hours; stirring at a speed of 900-1200 r / min during the reaction, and dialyzing the reaction solution with a 7000-10000Da dialysis bag after the reaction is completed to remove unreacted substances; Step 3.5, freeze-drying the product obtained in step 3.4 at -70°C to obtain white Yb-nanopolymer.

2. The method for preparing a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink according to claim 1, characterized in that: In the step 1.1, the catalyst is 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide.

3. The method for preparing a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink according to claim 1, characterized in that: The specific process of step 4 is as follows: Take 1-2g of Zn-nanopolymer, 2-4g of Yb-nanopolymer, 0.3-0.6g of boric acid, 1-2mL of toluene, 1-2mL of ethyl acetate and 5-10mL of PU tactile matt oil, mix and stir for 10-20min to obtain anti-counterfeiting ink.

4. A visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink, characterized in that: The invention is prepared by the method for preparing a visible long afterglow-near infrared dual-pass fluorescent anti-counterfeiting ink as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Zinc complex, preparation method thereof and application thereof in preparing anti-forgery ink

    CN102993219A

  • Luminescent lanthanide complex, and articles and inks containing the luminescent complex

    CN104703805A